Acantholimon assadii (Plumbaginaceae), a new species from flora of Iran - Bordbar, Firouzeh; Mirtadzadini, Mansour (Phytotaxa, 2022)
A new species, Acantholimon assadii from mountainous slopes of N of Kerman, Zarend, Kerman Province, south-east of Iran is here described and illustrated. The new species is morphologically distinguished from the other species of Acantholimon sect. Acantholimon by short spike-like inflorescence, length and width of bract and bracteoles, shape of bract and bracteoles, color of calyx and corolla.